The Oil Market and Macroeconomic Stability: What is the Role of Policy Uncertainty? - Su, Chi Wei; Bai, Ya Fei; Qin, Meng (Panoeconomicus, 2025)
We analyse the fluctuating connection between economic policy uncertainty (EPU) and oil prices (OP) in Croatia through sub-sample rolling-window Granger causality analyses. Statistical inference based on Granger causality tests suggests that OP acts as a leading indicator for EPU, with evidence of bidirectional feedback. The negative influence of OP on EPU indicates that OP will affect the government’s economic policy stability and then affect EPU. Conversely, EPU exhibits both positive and detrimental effects on OP. These results align with general equilibrium models, highlighting the interdependence between OP and EPU. Given the increasing financial attributes of oil, gaining insight into the connection between OP and EPU is essential for enabling the government to formulate more effective economic policies to mitigate the impacts of fluctuations in OP. JEL: Q43, C32, E69, H3